Environmental impacts of eucalypt and maritime pine wood production in Portugal - Dias, Ana Cláudia (2019)
This study evaluates the environmental impacts associated with the production of eucalypt (Eucalyptus globulus Labill.) and maritime pine (Pinus pinaster Ait.) wood in Portugal. Life Cycle Assessment (LCA) methodology is used from cradle-to-gate. Three forest management scenarios, representative of different forest management intensities and logging equipment, were simulated for each species. Furthermore, a sensitivity analysis was performed to evaluate the influence of adopting different values for the wood productivity. The results obtained for each impact category show a relatively wide range of variation when different management scenarios and wood productivities are taken into account. The impacts, except for those in the category photochemical oxidant formation, are much smaller in the less intensive scenario (40–88%). The impacts of using chainsaws and adapted farm tractors in logging operations instead of harvesters and forwarders do not significantly differ (less than 11%), except for the impact category photochemical oxidant formation for which there are significant differences. For the same type of management scenario, the impacts of eucalypt wood production are larger than those estimated for maritime pine wood. The logging stage, as well as fertilization, especially with nitrogen-containing fertilizers, plays a major role in all the impact categories. More accurate impacts could be quantified using the methodology adopted in this study when the provenance of the wood and, consequently, the forest operation type and frequency, and associated consumption of fuels, lubricants and fertilizers, are known.